A prospective study of the substance use and mental health outcomes of young adult former and current cannabis users. (20th March 2017) - Silins, Edmund; Swift, Wendy; Slade, Tim; Toson, Barbara; Rodgers, Bryan; Hutchinson, Delyse M.
Abstract: Introduction and Aims: The extent to which young adult former cannabis users fare better than infrequent users is unclear. We investigated the association between cannabis use status at age 23 and substance use and mental health outcomes at age 27. Design and Methods: Data were from the 20+ year cohort of the PATH Through Life Study. Lifetime cannabis users ( n  = 1410) at age 23 were classified as former/occasional/regular users. Multivariable logistic regression was used to estimate the association between cannabis use status at age 23 and six outcomes assessed at age 27. Results: Compared with occasional cannabis users: (i) former users had odds of subsequent tobacco use [odds ratio (OR) = 0.67, 95% confidence interval (CI) 0.52–0.85], illicit drug use (cannabis, OR = 0.22, 95% CI 0.17–0.28; other illicit drugs, OR = 0.29, 95% CI 0.22–0.39) and mental health impairment (OR = 0.71, 95% CI 0.55–0.92) that were 29–78% lower; and (ii) regular users had odds of subsequent frequent alcohol use (OR = 2.34, 95% CI 0.67–1.34), tobacco use (OR = 3.67, 95% CI 2.54–5.30), cannabis use (OR = 11.73, 95% CI 6.81–20.21) and dependence symptoms (OR = 12.60, 95% CI 8.38–18.94), and other illicit drug use (OR = 2.95, 95% CI 2.07–4.21) that were 2–13 times greater. Associations attenuated after covariate adjustment, and most remained significant. Discussion and Conclusions: Clear associations exist between cannabis use status in young adulthood and subsequent mental health and substance use. While early intervention remains important to prevent regular cannabis use and the associated harms, experimentation with cannabis use in the years leading into young adulthood may not necessarily determine an immutable pathway to mental health problems and illicit substance use. [Silins E, Swift W, Slade T, Toson B, Rodgers B, Hutchinson DM. A prospective study of the substance use and mental health outcomes of young adult former and current cannabis users. Drug Alcohol Rev 2017;00:000‐000]